2014
DOI: 10.1063/1.4868860
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic fluctuations of dust grain charge in multi-component plasmas

Abstract: A master equation is formulated to model the states of the grain charge in a general multi-component plasma, where there are electrons and various kinds of positive or negative ions that are singly or multiply charged. A Fokker-Planck equation is developed from the master equation through the system-size expansion method. The Fokker-Planck equation has a Gaussian solution with a mean and variance governed by two initialvalue differential equations involving the rates of the attachment of ions and electrons to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…These fluctuations always exist even in a steady-state uniform plasma 2 . Dust charge fluctuations have been investigated by many researchers [3][4][5][6][7][8][9] . In a dusty plasma, there are many phenomena that dust charge fluctuations can be considered as a reason for them such as heating of dust particles system [10][11][12] , instability of lattice oscillations in a low-pressure gas discharge 13,14 , and the formation of the shock waves in dusty plasmas 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These fluctuations always exist even in a steady-state uniform plasma 2 . Dust charge fluctuations have been investigated by many researchers [3][4][5][6][7][8][9] . In a dusty plasma, there are many phenomena that dust charge fluctuations can be considered as a reason for them such as heating of dust particles system [10][11][12] , instability of lattice oscillations in a low-pressure gas discharge 13,14 , and the formation of the shock waves in dusty plasmas 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 displays time histories of grain charges. The discrete stochastic method [13], adapted from Gillespie's algorithm [30,31]), is utilized to simulate the grain charge variation governed by the master equation (1). Time histories seen in figs.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of the grain charge variance is correlated with the currents and their derivatives evaluated at the charge mean. Shotorban [13] lately extended this model to include multi-component plasmas where there are various kinds of singly-or multiply-charged negative or positive ions and showed that the grain charge distribution still follows Gaussianity when Ω is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dust particle charge [23,25,26] is determined by electron and ion fluxes on the surface of dust grain, which depends on electric field. So the dust particle charge depends on z:…”
Section: Equations Of Dust Particles Motionmentioning
confidence: 99%